Travel Motivations of Educational Tourists Arriving in Georgia - Ana Gvaramadze (European Scientific Journal, ESJ, 2022)
Over the years, researchers have empirically studied the determinants of travel motivation and taken into account the diverse approaches and perspectives of travel motivation. The dynamic nature of travel motivation has led to a wide range of research in this area. Decisions made by tourists that are reflected in their travel behavior are essential for the tourism industry to maintain or improve the status quo. The paper aimed to identify the motivational factors that determine the decisions of educational tourists through quantitative research. According to the existing studies, significant travel motivations were identified and a survey was conducted with international students who choose Georgia as the destination for their studies at accredited higher educational institutions. The research has revealed that for international students, arriving in Georgia for educational purposes, the field of medicine is the first choice of interest.  Educational tourists choose Georgia for the following main reasons: security and political stability, the cost of learning and living, quality, and duration of the study.